Relationship between speed and agility in nationally ranked junior tennis players - Clark, S.; Martin, D.; Lee, H.; Fornasiero, D.; Quinn, A.
Ten metre sprint time was highly correlated with sprint times over both 5m (M, r=.93; F, r=.86) and 20m (M, r=.96; F=.94). Correlations were weak for males and females between sprint times and Acceleration/Deceleration (5m) (r<.35), Back Slide (r< .30), and Tball Forehand (r<.35) with the exception that Tball forehand for males was significantly correlated to 10m and 20m sprint times (r=.44 and r=.55). For the remaining agility tests correlations with sprint times were generally moderate for females (r=.35-.65) and strong for males (r=.55-.94). Correlations between agility tests and sprint times became stronger for males and females as the sprint distance increased (see Table 1).